Investigating the impact of microfinance on communities' welfare or quality of life in sub-Saharan Africa focusing on the case of Djibouti - Hassan, Fardowsa (2005)
More than 1.3 billion people, that is, one in every five on earth, survive on less than a $1 a day (UNDP, 2004). International development institutions and government of foreign aid donors have tried ways to alleviate poverty. Despite of decades, of development aid targeted at increasing economic growth of aid beneficiary countries; the number of poor in sub-Saharan Africa has increased. With the failure of traditional form of aid and development policies, the focus is now on grassroots development targeted type. Microfinance is one of these types of development idea targeted directly at the poor. It is a small scale credit scheme targeted at the poor who have been rejected from the traditional financial institutions. This dissertation investigates the impact of microfinance on communities' welfare or quality of life in sub-Saharan Africa focusing on the case of Djibouti. The study begins by reviewing the background information on Djibouti, followed by the literature review on microfinance.